Refugee Documentation Project - Refuge Editor (Refuge: Canada’s Journal on Refugees, 1983)
The Refugee Documentation Project at York University is concerned with ac- quiring and preserving archival materials pertaining to refugees in and from all parts of the world. (The Pro- ject’s library is open between 10 a.m. and 5 p.m. on weekdays.) Donations of documents, papers, reports or other library materials are encouraged.